DESIGN AND BUILD A SEED PLANTING ROBOT PROTOTYPE USING ESP8266 BASED ON THE INTERNET OF THINGS - aan, Aan Eko Setiawan (Universitas Lampung, 2025)
This research develops a seed planting robot prototype based on the Internet of Things (IoT) using the ESP8266 module, aimed at reducing the physical burden on farmers in the manual seed planting process. IoT and robotic technologies are expected to improve efficiency and reduce the health risks associated with repetitive physical activities. The system is operated through a mobile application based on MIT App Inventor, which allows wireless control of the robot. The research includes the design of hardware, software, and system performance testing. Test results show that the robot can connect to Wi-Fi up to a distance of 12 meters, with the DC and servo motors functioning as commanded. The delay time for motor commands ranges from 0.13 to 0.20 seconds, indicating good responsiveness. However, the limited Wi-Fi range becomes a constraint for operating the robot at greater distances. In conclusion, this robot system performs well in seed planting and can enhance operational efficiency in agriculture, although further development is needed to extend communication range and improve system functionality.